2007
DOI: 10.3324/haematol.10913
|View full text |Cite
|
Sign up to set email alerts
|

Surgical bleeding after pre-operative unfractionated heparin and low molecular weight heparin for coronary bypass surgery

Abstract: Background and ObjectivesSince the impairment of platelet function may cause excess peri-operative bleeding, pre-operative discontinuation of aspirin and heparin bridging are common for cardiac surgery. We evaluated the impact of pre-operative administration of enoxaparin and unfractionated heparin (UFH) on coagulation parameters and peri-operative bleeding in patients undergoing elective coronary artery bypass grafting (CABG) surgery after discontinuation of aspirin. Design and MethodsForty-three patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
0
6
0
2
Order By: Relevance
“…Some of these studies showed no significant risk of bleeding in those patients compared to subjects receiving UFH [9][10]. In fact, Renda et al found that transfusional requirements of blood and plasma was similar in patients receiving either UFH or LMWH (stopped 12 hours prior to surgery) but their study had sample size limitation [9]. Medalion et al found also that administration of enoxaparin more than 8 hours before surgery did not increase bleeding or products' transfusion rate [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies showed no significant risk of bleeding in those patients compared to subjects receiving UFH [9][10]. In fact, Renda et al found that transfusional requirements of blood and plasma was similar in patients receiving either UFH or LMWH (stopped 12 hours prior to surgery) but their study had sample size limitation [9]. Medalion et al found also that administration of enoxaparin more than 8 hours before surgery did not increase bleeding or products' transfusion rate [10].…”
Section: Discussionmentioning
confidence: 99%
“…B. Enoxaparin 1 mg/ kg 2-mal täglich, Dalteparin 100 IE/kg 2-mal täglich u. a. [1] Über den für eine Gerinnungsnormalisierung notwendigen zeitlichen Abstand zwischen der letzten Gabe niedermolekularen Heparins und dem Eingriff liegen unterschiedliche Daten vor [18,20,21]: 24 h Abstand mit Reduktion der letzten Dosis auf die Hälfte sind zu bevorzugen [1].…”
Section: Niedermolekulares Heparinunclassified
“…Sie hat sich aufgrund der kalkulierbaren Antikoagulation bereits zu Therapiebeginn wie auch wegen der größeren Mobilität der Patienten bei s.c.-Gabe als zu bevorzugende Alternative zu unfraktioniertem Heparin erwiesen [1,8,20,22,23,27]. Dieses Vorgehen ist nach der aktuellen US-amerikanischen Leitlinie [1] inzwischen auch für das Bridging bei Patienten mit mechanischem Herzklappenersatz anwendbar, allerdings favorisierte die letzte europäische Leitlinie noch unfraktioniertes Heparin [15].…”
Section: Niedermolekulares Heparinunclassified
“…We identified 16 studies that met our inclusion criteria, which are presented in Additional file 1 , Table 1 [ 21 - 36 ]. Seven of these studies were cardiovascular surgery studies [ 25 , 27 , 28 , 31 , 32 , 35 , 36 ], three were pancreatic surgery [ 21 , 24 , 29 ], and the others included major abdominal surgery [ 23 ], major orthopedic surgery [ 33 ], non-cardiac general surgery [ 34 ], laparoscopic cholecystectomy [ 26 ], prostatic resection [ 22 ], and laparoscopic and thoracoscopic surgery [ 30 ]. Seven of the studies included more than 1,000 patients[ 23 , 24 , 26 , 28 , 30 , 31 , 33 ].…”
Section: Incidence Of Bleeds In Surgery Studiesmentioning
confidence: 99%